2010
DOI: 10.1167/iovs.09-4008
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Accommodative Function of the Vitreous Zonule in Human and Monkey Eyes

Abstract: Purpose To explore the attachments of the posterior zonule and vitreous in relation to accommodation and presbyopia in monkeys and humans. Methods We used novel SEM and UBM techniques to visualize the anterior, intermediate and posterior vitreous zonule and their connections to the ciliary body, vitreous membrane, lens capsule and ora serrata, and to characterize their age-related changes and correlate them with loss of accommodative forward movement of the ciliary body. We injected α-chymotrypsin focally to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
77
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 22 publications
5
77
0
Order By: Relevance
“…The posterior vitreous zonular fibers (off-white) form a sponge-like structure at the vitreous base with obliquely crossing fibers forming a network capable of dampening the forces of accommodation and preventing trauma to the peripheral retina, as suggested by L€ utjen-Drecoll et al 8 As a group, the posterior zonular fibers, in concert with the anterior zonular fibers, create the reciprocal zonular action that occurs during accommodation and disaccommodation. The posterior zonular fibers transfer tension and release from the ciliary muscle to the elastic foundation in the choroid.…”
Section: Posterior Zonular Fibersmentioning
confidence: 99%
See 2 more Smart Citations
“…The posterior vitreous zonular fibers (off-white) form a sponge-like structure at the vitreous base with obliquely crossing fibers forming a network capable of dampening the forces of accommodation and preventing trauma to the peripheral retina, as suggested by L€ utjen-Drecoll et al 8 As a group, the posterior zonular fibers, in concert with the anterior zonular fibers, create the reciprocal zonular action that occurs during accommodation and disaccommodation. The posterior zonular fibers transfer tension and release from the ciliary muscle to the elastic foundation in the choroid.…”
Section: Posterior Zonular Fibersmentioning
confidence: 99%
“…In 2010, L€ utjen-Drecoll et al 8 identified 3 elements of vitreous zonular fibers in addition to the pars plana zonule. The classification of zonular fibers as anterior/ posterior or as lenticular/vitreous/pars plana is confusing, Using model-based cognitive thinking, a new classification based on structure and function is proposed.…”
Section: Model Of Accommodation and Extralenticular Anatomy And Zonulmentioning
confidence: 99%
See 1 more Smart Citation
“…As the same time the anterior zonules relax, reducing their tension on the lens such that the lens changes shape anteriorly, the posterior zonules contract, moving the posterior capsule backward. This vitreal-zonular complex stiffens with age, losing its elasticity (1)(2)(3) . The age-related changes in these structures and their biomechanical interactions with the ciliary-lens complex may contribute to presbyopia (3).…”
mentioning
confidence: 99%
“…This vitreal-zonular complex stiffens with age, losing its elasticity (1)(2)(3) . The age-related changes in these structures and their biomechanical interactions with the ciliary-lens complex may contribute to presbyopia (3). It has been newly discovered that there are also changes in extralenticular structures which may have an impact on the loss of accommodation which were previously deemed to be of very little importance, namely the sclera and choroid (2) .…”
mentioning
confidence: 99%